2011
DOI: 10.1007/s00404-011-2051-2
|View full text |Cite
|
Sign up to set email alerts
|

Hormone replacement therapy: relation to homocysteine and prooxidant-antioxidant status in healthy postmenopausal women

Abstract: Our results show that HRT is beneficial in the protection against oxidative damage, and prevents atherosclerotic complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 39 publications
0
5
1
Order By: Relevance
“…Escalante Gómez and Quesada Mor found lower 8-OH-2dG levels in women receiving combined HRT compared to women who did not receive therapy [126], while TBARS were lower in women on ERT compared to non-users. Another recent study reported a decrease of TBARS, but unvaried levels of serum homocysteine and carbonyls in postmenopausal women under HRT compared to women receiving oral placebo [127]. At variance with this report, Unfer et al [128] found no difference in serum TBARS between healthy postmenopausal women without/with HRT.…”
Section: Hrt (And/or Ert) and Oxscontrasting
confidence: 52%
“…Escalante Gómez and Quesada Mor found lower 8-OH-2dG levels in women receiving combined HRT compared to women who did not receive therapy [126], while TBARS were lower in women on ERT compared to non-users. Another recent study reported a decrease of TBARS, but unvaried levels of serum homocysteine and carbonyls in postmenopausal women under HRT compared to women receiving oral placebo [127]. At variance with this report, Unfer et al [128] found no difference in serum TBARS between healthy postmenopausal women without/with HRT.…”
Section: Hrt (And/or Ert) and Oxscontrasting
confidence: 52%
“…Females had lower Hcy levels compared with males, and Hcy was not a significant risk factor for females. This difference might be due to female hormones, which were demonstrated to have antioxidant effects that may antagonize the risk based on Hcy [32] . Further studies are needed to investigate the mechanism, but gender is an important factor that should be considered in future studies on the relationship between Hcy and hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…The main studies about effect of HRT has been carried out with combination estrogen plus gestagen, and in them has been founded in example that carbonils groups determined by ELISA showed a reduction of serum levels after six months oral or transdermal treat when compared with control group, and there was not difference between oral and transdermal, which indicates that hormonal therapy reduces the of carbonyl protein, a marker of oxidative stress, suggesting potential protective effect [71]. Similar result were founded with the serum level of malondialdehyde, superoxide dismutase and sulfhydryl groups without changes on plasma total homocysteine (tHcy) (used as atherogenic indicator) [72]. Another study with equal number of months of follow-up showed that carbonyls, MDA and oxLDL were reduced, while erythrocyte glutathione (GSH) were increased, and nitrotyrosine (NT) levels were not changed [73,74] (Table 6).…”
Section: Six Monthsmentioning
confidence: 60%